Aborsi Dalam Kasus Pemerkosaan Anak: Perspektif Undang-Undang Nomor 17 Tahun 2023 dan Hak Asasi Manusia - Natasya Putri Veruanti Manurung; A. Sakti R.S. Rakia; Wahab Aznul Hidaya (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This study examines the legalization of abortion due to rape of minors based on Undang-Undang No. 17 Tahun 2023 tentang Kesehatan dan perspektif HAM, and legal protection for children who have abortions in these situations. Using normative research methods, the results show that abortion can be allowed in accordance with the Pasal 60 Undang-Undang No. 17 Tahun 2023 with certain conditions, such as indications of medical emergencies and psychological trauma. From a human rights perspective, abortion can only be approved if it aims to save the lives of the fetus and the mother. Legal protection for children who have abortions due to rape is emphasized as a form of safeguarding the rights of children as victims, taking into account the reasons and conditions that force the child to commit the act. In conclusion, the law must ensure justice by considering the condition of the perpetrator, especially in cases of forced abortions.